Activin Receptor-Like Kinase 1 Combined With VEGF-A Affects Migration and Proliferation of Endothelial Cells From Sporadic Human Cerebral AVMs - Hao, Qiang; Wang, Hao; Lu, Jun-Lin; Ma, Li; Chen, Xiao-Lin; Ye, Xun; Zhao, Ya-Hui; Li, Ming-Tao; Chen, Yu; Zhao, Yuan-Li (Frontiers in Cellular Neuroscience, 2019)
Heterozygous loss of activin receptor-like kinase 1 (ALK1) can lead to hereditary hemorrhagic telangiectasia (HHT)，which is a kind of vascular disease characterized by direct connections between arteries and veins with the lacking of capillaries, and develops into arteriovenous malformations (AVMs) in later stage. However, the changes of ALK1 in human sporadic cerebral AVMs (cAVMs) remain unknown. In the present study, we used endothelial cells (ECs) derived from human cerebral AVMs (cAVM-ECs) specimens, to explore the characteristics of cAVM-ECs and the relationship between ALK1 and human sporadic cAVMs. Our data showed that there were obvious morphological changes in cAVM-ECs, and they could trans-differentiate into mesenchyme-like cells easily in a short period. In addition, the abilities of migration of cAVM-ECs were poorer than that in human aortic endothelia cells (HA-ECs). The abilities of proliferation of cAVM-ECs in patients with different ages were lower than HA-ECs. Immunofluorescent staining and Western blot showed that the levels of Alk1 mRNA and protein in the HA-ECs were both higher than that in cAVM-ECs. In addition, the levels of ALK1 mRNA had no significant differences between different ages in cAVM-ECs groups. The levels of VEGF-A mRNA in the cAVM were higher than HA-ECs. Besides, levels of VEGF-A mRNA expression were lower in older cAVM patients. Therefore, we conclude that ALK1 might induce the formation of sporadic human cAVMs through affecting migration and proliferation of endothelial cells combined with VEGF-A.